APPLICATION OF QuEChERS METHOD FOR MULTI-RESIDUE PESTICIDES DETERMINATION IN LETTUCE AND APPLE USING GAS CHROMATOGRAPHY-MASS SPECTROMETRY (Nigerian Journal of Technology, 2016)
This study investigated the use of the QuEChERS method for the analysis of 13 pesticides on apples and lettuces. Comparison between two methods: Citrate- (buffered and unbuffered) and acetate (buffered and unbuffered). A range of pesticides –pirimicarb, diazinon, chlorpyrifos, azoxystrobin, pendimethalin, cyprodinil, boscalid, chlorothalonil, fenhexamid were selected for this study. Triphenyl phosphate was used as the internal standard. Results obtained revealed very high percentage recoveries for the majority of the pesticides screened for with recoveries of 66.3 to 109.8% for the citrate buffered, 72.5 – 120.8% for citrate unbuffered, 53.8 – 102% for acetate buffered and 54 – 105.3% for acetate unbuffered experiments carried out using apple samples. % recoveries obtained for the lettuce samples were 32.2 to 120.5% for the citrate buffered, 33.7 – 115.0% for citrate unbuffered, 53.8 – 107.4% for acetate buffered and 54 – 105.3% for acetate unbuffered experiments. % recoveries obtained for the apple samples were 64.3 – 109.8% for the citrate buffered, 72.5 – 120.8% for the citrate unbuffered, 60.3 – 102.0% for the acetate buffered and 54 – 120.5% for acetate unbuffered. Pendimethalin and cyprodinil gave the poorest recoveries while chlorothalonil gave the best recoveries for both the different methods and samples. The organophosphorus pesticides (diazinon and chlorpyrifos) gave relatively good recoveries especially for the apple samples. Comparison of sample recoveries revealed a more favourable recovery for the apple samples compared to the lettuce samples. The limit of detection was also determined to be ~0.02µg/L (6µg/kg). http://dx.doi.org/10.4314/njt.v35i3.11